2012
DOI: 10.1126/science.1221774
|View full text |Cite
|
Sign up to set email alerts
|

Subtractive Patterning via Chemical Lift-Off Lithography

Abstract: Conventional soft-lithography methods involving the transfer of molecular "inks" from polymeric stamps to substrates often encounter micrometer-scale resolution limits due to diffusion of the transferred molecules during printing. We report a "subtractive" stamping process in which silicone rubber stamps, activated by oxygen plasma, selectively remove hydroxyl-terminated alkanethiols from self-assembled monolayers (SAMs) on gold surfaces with high pattern fidelity. The covalent interactions formed at the stamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
270
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(271 citation statements)
references
References 49 publications
1
270
0
Order By: Relevance
“…For the reduced gold surface, the force histogram indicates a most probable rupture force of 0.62±0.18 nN. Previous studies 5,27,[30][31][32]34,43,44 strongly indicated that the breakage takes place at the Au-Au bond around the Au-S binding sites, which was the weakest among the covalent bonds (that is, Si-O, Si-C, C-N, C-C, C-O, Au-S and Au-Au) in the linkage, leaving one or more gold atoms at the terminal of the tethered linker. Control experiments, in which the thiolterminated PEG was replaced with sulphur-free methoxylterminated PEG, were performed to confirm that the rupture force obtained above originated from the interaction between the sulphydryl group and gold surfaces.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For the reduced gold surface, the force histogram indicates a most probable rupture force of 0.62±0.18 nN. Previous studies 5,27,[30][31][32]34,43,44 strongly indicated that the breakage takes place at the Au-Au bond around the Au-S binding sites, which was the weakest among the covalent bonds (that is, Si-O, Si-C, C-N, C-C, C-O, Au-S and Au-Au) in the linkage, leaving one or more gold atoms at the terminal of the tethered linker. Control experiments, in which the thiolterminated PEG was replaced with sulphur-free methoxylterminated PEG, were performed to confirm that the rupture force obtained above originated from the interaction between the sulphydryl group and gold surfaces.…”
Section: Resultsmentioning
confidence: 95%
“…SAMs that are based on thiol-gold chemistry have been widely employed in the fields of chemistry, physics, molecular biology, pharmaceutical engineering and materials science [1][2][3] . Considerable interests in such systems have increased, owing to their versatile applications, including the fabrication of nanopatterning 4,5 , molecular-scale devices 6,7 , optical materials 8,9 , formulation of biosurfaces 10 and support for cell culture 2,11 . The strength of the gold-sulphur (Au-S) interaction formed between thiols and gold surfaces provides the basis to fabricate robust SAMs for diverse applications.…”
mentioning
confidence: 99%
“…The monolayers studied consist of undecanethiol alkyl chains that are chemically bound to an Au(111) surface. After the deposition of alkyl chains, the rhenium carbonyl vibrational probe (fac-Re(phenC≡CH)(CO) 3 Cl) is attached to the monolayer via a Cu(I)-catalyzed alkyne-azide cycloaddition (CuAAC) reaction ("click" chemistry). In addition to the head group rhenium carbonyl complex (the vibrational probe), there is also a triazole ring, which is formed during the cycloaddition reaction (Fig.…”
Section: Static Structure Of Gold Samsmentioning
confidence: 99%
“…For high‐resolution nanopatterns a number of techniques are well developed, including electron‐/ion‐beam‐based litho­graphy1, 2, 3 and tip‐based lithography,4, 5, 6, 7, 8, 9 but they are often too slow for wafer‐scale processes that demand fast processing times. On the other hand, for large‐area nanopatterning, optical/plasmonic lithography,10, 11, 12, 13, 14, 15 contact printing‐based lithography,16, 17, 18, 19 and template‐assisted lithography20, 21, 22, 23 are promising candidates; however, they require additional expensive and time‐consuming pre‐fabrication processes, such as the preparation of a master template. Colloidal lithography including nanosphere lithography (NSL),24 nanoparticle lithography,25, 26 and block copolymer micelle nanolitho­graphy (BCML)27 are attractive large‐scale parallel patterning methods that permit time‐ and cost‐effective patterning at the wafer‐scale.…”
mentioning
confidence: 99%